"Any Sacrifice Is Worthwhile Doing": Latina Au Pairs Migrating to the United States for Opportunities. Issue 3 (3rd July 2018) - Cuban, Sondra
ABSTRACT: A study of 20 highly educated Latin American women who entered the United States on au pair visas showed that they struggled to improve their opportunity structures. The study draws on skilled female migration theory to focus on the participants' ambitions, work experiences, and their trajectories in the United States. The findings focused on the contradictions between the participants' aspirations and the realities of their work lives, legal status, and prospects in the United States that impacted their advancement. They exercised their agency despite difficult circumstances.